KEBUTUHAN MANAJEMEN SEKOLAH DASAR BERBASIS PENDIDIKAN KARAKTER PADA SEKOLAH DASAR - Iin Karlina; Rizka Ramadhani; Firda Siti Zulfa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary school management’s the process of managing all educational resources in a planned, systematic, sustainable manner to achieve educational goals effectively and efficiently. This study aims to analyze the implementation of elementary school management at MIN 7 Tangerang, which includes curriculum management, students, educators and education personnel, facilities, infrastructure, graduate management. The study used a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, documentation studies of various school activities. The results of the study indicate that MIN 7 Tangerang has implemented the Independent Curriculum combined a religious excellence program in the form of BTQ and Tahfiz Juz 30. Student management’s carried out starting from online admission of new students, administrative recording through master books and clapper books, heterogeneous student placement, to character development through the SELASIH (Selasa Bersih) program, Al-Qur'an recitation, and congregational prayer. The school also implements a culture of discipline based on the values ​​of IMTAQ and akhlakul karimah. Educators and staff possess strong competencies and high dedication to their duties, despite challenges in utilizing technology and managing administrative burdens. While school facilities, infrastructure are adequate, there’s limitations on land and extracurricular support facilities. Successful school management’s supported by the leadership of the principal, the cooperation of the entire school community, and a commitment to improving the quality of education. With effective management, the school’s able to produce graduates with character, strong academic, religious skills, and are prepared to continue their education to a higher level.